HUBUNGAN PENANGANAN SAMPAH KOTA DENGAN PERILAKU MASYARAKAT : Studi Kasus Pengelolaan Sampah Kota Cimahi - Ramang, Ruslan (Bumi Lestari, 2013)
Abstract This article aims to look at find out the existing condition of the way the community hanlde their wastes, at the level of household, to analyse points which back the community participation, having constrains of the handling of the existing wastes and waste-related problems which the community of the respective city face. The questionaire-based survey, was engaged into the research as the survey method while the stratified random sampling was engaged throughout the analysis of the same as the sampling technique. The results shows that existence of an operational public waste collecting system tends to lessen the waste-related problem in the respondents’ residential enviroment. Four factors which differentiate the respondents who participate from those who do not, in respect to waste treatment are: behaviour of disposing waste to river, behaviour of burrying the wastes, the problem of smell and the problem of river pollution. Existence of a good public waste collecting system which can overcome the waste-related problems in the residential environemnt of the community, can motivate the same to participate in better treating and manage their wastes.
Keywords: Key words: participation, waste-handling, waste-problem, transportation